Analisis Usability Website PT. Perkebunan Nusantara (PTPN IX) Untuk Menunjang Industri Kreatif di Era Global - Fadiana; Kristiyanto, Daniel Yeri (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2025)
Technology is rapidly advancing in society and the workplace. PT Perkebunan NusantaraIX (PTPN IX), which operates in the management and marketing of plantationcommodities, has utilized technology to facilitate the presentation of downstream productinformation through a dynamic website. The PTPN IX website plays a crucial role inpresenting the company's latest information. However, the PTPN IX website has neverundergone a usability testing process. Therefore, this study aims to analyze the quality ofthe website in supporting its role and functions. The results of the observations indicate thatseveral users experience problems when accessing the website. To analyze these issues,heuristic evaluation methods were used to identify usability problems on the website, andthe System Usability Scale (SUS) to assess the system's feasibility. This method involved3 evaluators and 100 users to evaluate the website based on 10 heuristic aspects, whichwere mapped into sub-aspects according to their severity levels. The overall evaluationresults indicated categories of cosmetic issues and minor usability problems. This studyidentified 10 problems and provided recommendations for improving the PTPN IXwebsite. The improvement recommendations aim to optimize the website system to betterfulfill its role and function as an information provider platform related to local commodityproducts for all elements of society.